Real-world data of cadonilimab in recurrent or metastatic cervical cancer in China: a multicentric study - Chen, Jian; Yu, Haijuan; Lin, Yingtao; Hu, Dan; Liu, Li; Fan, Renliang; Zou, Jianping; Zang, Lele; Lin, Yao; Lin, Rong; Chen, Dezhao; Weng, Xiaoying; et al. (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has become a powerful clinical strategy for treating recurrent or metastatic cervical cancer (R/M CC). Cadonilimab, a novel anti-PD-1/CTLA-4 bispecific antibody, has shown substantial clinical benefits in cancer treatment. However, there is no real-world evidence of cadonilimab with a considerable sample size in R/M CC. Hence, we aim to assess the efficacy and safety of cadonilimab in R/M CC patients and explore its potential mechanism.MethodsThis retrospective real-world study examined a sample of R/M CC patients treated with cadonilimab at 13 large academic medical centers in China from July 6, 2022, to October 1, 2023. The outcomes were objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), as well as safety profiles. Additionally, the programmed cell death 1 ligand 1 (PD-L1) was detected by immunohistochemistry to confirm its predictive values. Whole exome sequencing (WES) was also performed to investigate its potential antitumor mechanisms.ResultsAmong the 129 patients with measurable disease, the ORR was 38.8%, consisting of complete and partial responses in 8.5% and 30.2% of patients, respectively. The DCR was 72.1%. The median PFS was 12.4 months, while the median OS has not yet been reached. Subgroup analysis showed a numerical trend toward longer median PFS in patients with PD-L1 CPS ≥ 1 compared with CPS < 1 (14.0 vs. 12.8 months; P = 0.235). Moreover, combined therapy of cadonilimab and radiotherapy was identified as an independent prognostic factor for both OS and PFS. The most common grade 3 or worse adverse event was anemia (28 [20.1%]), decreased white blood cell count (24 [17.2%]), and decreased neutrophil count (20 [14.4%]). The most prevalent genetic variant was PIK3CA, highlighting the importance of the PI3K-AKT pathway in the antitumor mechanism of cadonilimab.ConclusionsCadonilimab shows an encouraging tumor response rate, with a manageable safety profile in patients with R/M CC. Notably, cadonilimab is also effective for those with PD-L1 CPS <1, suggesting a broad range of application prospects in R/M CC.Clinical Trial Registrationhttps://www.clinicaltrials.gov, identifier NCT06140589.